Work Stress on Turn Overintention : Moderated by Emotional Intelligence in Nurses at The DR. Drs. M. HATTA BUKITTINGGI Brain Hospital - m.azman zaim; fitria, yuki (Human Resource Management Studies, 2025)
This study aims to examine: (1) the effect of job stress on turnover intention (2) the effect of job stress on turnover intention moderated by emotional intelligence. This research is a causal research. The population of this study were Rs nurses at Dr. Drs. M. Hatta Bukittinggi Brain Hospital. The number of samples used was the total population of 136 people taken using proportional random sampling. Data collection using a questionnaire with a Likert Scale. The analysis technique used through SmartPLS 4 software. The results of data processing in this study indicate that: (1) Work stress has a positive and significant effect on Turnover Intention in Rs nurses at Dr. Drs. M. Hatta Bukittinggi Brain Hospital. (2) Emotional intelligence is able to moderate the influence between work stress on turnover intention.